2015
DOI: 10.1080/19443994.2014.1002430
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive study on the removal of chromate from aqueous solution by synthesized kaolin supported nanoscale zero-valent iron

Abstract: A removal mechanism of chromate (Cr) by synthesized kaolin supported nanoscale zerovalent iron (K-nZVI) from aqueous solution is demonstrated. Parameters which potentially influenced the functioning of K-nZVI have been investigated as well. Based on the scanning electron microscopy, Fourier transform infrared spectroscopes, X-ray crystal powder diffraction and X-ray photoelectron spectroscopy identifications, we confirm that amorphous Fe 0 core/Fe x O y shell nZVI can be successfully loaded into the pores and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 42 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…Some studies obtained results similar to the present study. They reported that efficiency of Lead removal was decreased with increasing initial Lead and Cr 6+ concentrations with nZVI and KnZVI dosages (19,23). Though, the study of Chuang et al (2015) revealed that 100 mg/l was the optimal concentration for Lead removed by C-nZVI (Coated nZVI) (24), in our study based on Figure 5, 10 mg/L was the optimum concentration for Lead.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Some studies obtained results similar to the present study. They reported that efficiency of Lead removal was decreased with increasing initial Lead and Cr 6+ concentrations with nZVI and KnZVI dosages (19,23). Though, the study of Chuang et al (2015) revealed that 100 mg/l was the optimal concentration for Lead removed by C-nZVI (Coated nZVI) (24), in our study based on Figure 5, 10 mg/L was the optimum concentration for Lead.…”
Section: Discussionmentioning
confidence: 75%
“…This study showed that when the adsorbent dosage increased from 0.1 to 5 g/L, the removal efficiency of Lead ion decreased. However, numerous studies indicated that Lead and Cr 6+ removal increased significantly with increasing nZVI and K-nZVI dosages, when other parameters were constant (19,23). In this study, other parameters were variable.…”
Section: Discussionmentioning
confidence: 95%
“…The concentrations of Cr(III), Cr(VI), and Cu(II) were 300 mg⋅L −1 , 200 mg⋅L −1 , and 200 mg⋅L −1 , respectively. Then, samples were completely mixed using a magnetic stirrer at a speed of 200 rpm and collected at different time intervals (i.e., 5,10,15,20,30,40,60,80, 100, and 120 min). Finally, samples were immediately filtered with 0.45 m polycarbonate filters for further analysis.…”
Section: Batch Adsorption Experimentsmentioning
confidence: 99%
“…In addition, pH is an important aqueous chemistry variable that affects both the surface charge of adsorbent and the speciation of heavy metal, resulting in the different adsorption behavior of metals on adsorbent surfaces and intraparticle processes [11,12]. For example, the removal efficiency of both Cr(III) and Cr(VI) by kaolin increased with increasing pH up to 5.0 [13,14], yet when using synthesized kaolin, the adsorption capacity of Cr(VI) decreased as pH increased [15]. A lot of work has been done on the use of low-cost adsorbents for removal of Cr (III) or Cr(VI) in a single system, while the adsorption behaviors of Cr(III) or Cr(VI) on soils and clay minerals in the presence other heavy metals have increasingly gained attention.…”
Section: Introductionmentioning
confidence: 99%
“…Zero-valent iron has reducibility, which means that it can reduce its toxicity by changing the valency of As (Ramos et al, 2009). High surface energy can adsorb As and reduce their migration ability (Gupta et al, 2012;Wang et al, 2016). Many studies have discussed the effect of nZVI concentration on soil As pollution control (Fan et al, 2020;Li et al, 2021c).…”
Section: Introductionmentioning
confidence: 99%